Colour Vision Changes across Lifespan: Insights from FM100 and CAD Tests - Trukša, Renārs; Fomins, Sergejs; Jansone-Langina, Zane; Tenisa, Laura (MDPI, 2024)
(1) Background: in this research study, colour vision was evaluated in individuals aged 19 to 70 years with and without red–green colour vision disorders. (2) Methods: study participant colour vision was assessed with anomaloscope, HRR, FM100 hue, and CAD tests. (3) Results: No significant correlation was found between participant age and chromatic sensitivity of the red–green colour opponent channel. However, a decrease in blue–yellow colour opponent channel chromatic sensitivity was confirmed with the FM100 hue test and CAD test. Analysis of FM100 hue test error scores across age groups revealed a decline in chromatic sensitivity in the short-wave region of visible light with increasing age. Comparison of the colour-deficient individual results of the CAD and anomaloscope tests confirmed that CAD test sensitivity and specificity reaches 100%. However, some individuals with deutan-type deficits were misclassified as having protan-type deficits. This study confirmed the effectiveness of the FM100 test in identifying individuals with moderate to severe colour vision deficits, with sensitivity and specificity rates of 81.25% and 95.38%. (4) Conclusions: It was found that the FM100 hue test effectively identifies individuals with moderate and severe red–green colour vision deficiencies. On the other hand, individuals with mild colour vision deficiencies may go undetected with the FM100 hue test. © 2024 by the authors. --//-- This is an open-access article Trukša, R.; Fomins, S.; Jansone-Langina, Z.; Tenisa, L. Colour Vision Changes across Lifespan: Insights from FM100 and CAD Tests. Vision 2024, 8, 53. https://doi.org/10.3390/vision8030053 published under the CC BY 4.0 licence.
This research is supported by the Department of Optometry and Vision Science within the framework of the ORZN scientific research project “Cataracts affected crystalline lens effects on colour vision and colour perception” (Project No. ORZN-2023/2).The Institute of Solid State Physics, University of Latvia at the Center of Excellence, has received funding from the European Union's Horizon 2020 Framework Programme H2020-WIDESPREAD-01-2016-2017-TeamingPhase2 under grant agreement No. 739508, project CAMART2.
Keywords: Research Subject Categories::NATURAL SCIENCES; chromatic sensitivity; colour opponent channel; colour vision deficiency; colour vision tests